Republic of Estonia : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2006)
Estonia's commitment to free markets and prudent financial policies has paid off handsomely. Demand pressures and rapid productivity growth have produced strong wage increases and large employment gains. Inflation, while moderate for a fast-converging economy, remains above the Maastricht threshold, and has been pushed up in recent months by rises in nontraded goods prices. Estonia's economic growth has supported-and been supported by-rapid credit growth, financed increasingly by resource transfers from Nordic banking groups to Estonian affiliates. The macroeconomic impact of EU funds is needed.